2012
DOI: 10.1097/icl.0b013e3182499b64
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of the Central Epithelium Imaged With Three Optical Coherence Tomography Devices

Abstract: The algorithm seemed to be feasible for automatically segmenting the CCT and ET in OCT images using these tested OCT devices. The segmented results were equivalent to that obtained with the manual method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The repeatability of measuring the thickness of the epithelium and Bowman’s layer has been validated by our previous studies using the same method [15,19], and the thickness of the DEC is similar to Bowman’s layer. Shousha et al demonstrated the capability of measuring the DEC thickness using UHR-OCT [20].…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…The repeatability of measuring the thickness of the epithelium and Bowman’s layer has been validated by our previous studies using the same method [15,19], and the thickness of the DEC is similar to Bowman’s layer. Shousha et al demonstrated the capability of measuring the DEC thickness using UHR-OCT [20].…”
Section: Methodsmentioning
confidence: 88%
“…It was similar to the device used in previously published studies [15,16]. A superluminescent diode light source (Broadlighter, T840-HP, Superlumdiodes Ltd, Moscow, Russia) with a full width at half maximum bandwidth at 100 nm, centered at 840 nm, was used to provide low coherence light.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the computation time, a limited search region was defined. The border of the central posterior corneal surface was estimated from the peak of axis intensity profiles around the central apex [32,33]. The search was limited to the region below the detected border.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%